Examining Positive Emotions on Student Engagement during COVID-19 Situation with Academic Psychological Capital as a Mediating Variable - Nerinda Rizky Firdaus; Wiwin Hendriani; Nono Hery Yoenanto (Faculty of Psychology, Universitas Gadjah Mada, 2022)
Student engagement is an important aspect of an individual's school adaptation and adjustment to changes . Students who engage in learning will be more likely to succeed in their studies and get good performance. This study aimed to determine the effect of positive emotions on student engagement with academic psychological capital as a mediator. This study adopted a survey method in which 396 seventh grade students of nine junior high schools in Surabaya city participated in cluster random sampling and stratified random sampling was employed as recruitment strategies. The data collected were analyzed using Structural Equation Modeling with Partial Least Squares approach. Results indicate that academic psychological capital partially mediates the influence of positive emotions on student engagement. Partial mediation shows that positive emotions have a direct influence on students' engagement to the existence of academic psychological capital as a mediator.